American happiness and discontents : the unruly torrent, 2008-2020 - Will, George F. (Hachette Books, 2021)
"From the Pulitzer Prize-winning columnist George F. Will, his ninth collection of reflections on our culture, examining the many ways in which expertise, reason, and manners are continually under attack in our institutions, courts, political arenas, and social venues. George F. Will has been one of this country's leading columnists since 1974. He won the Pulitzer Prize for it in 1977. The Wall Street Journal once called him "perhaps the most powerful journalist in America." In this new collection, he examines a remarkably unsettling thirteen years in our nation's experience, from 2008 to 2020. Included are a number of columns about court cases, mostly from the Supreme Court, that illuminate why the composition of the federal judiciary has become such a contentious subject. Other topics addressed include the American Revolutionary War, historical figures from Frederick Douglass to JFK, as well as a scathing assessment of how State of the Union Addresses are delivered in the modern day. Mr. Will also offers his perspective on American socialists, anti-capitalist conservatives, drug policy, the criminal justice system, climatology, the Coronavirus, the First Amendment, parenting, meritocracy and education, China, fascism, authoritarianism, Frank Sinatra, Bob Dylan, The Beach Boys, and the morality of enjoying football. American Happiness and Discontents: The Unruly Torrent, 2008-2020 is a collection packed with wisdom and leavened by humor from one the preeminent columnists and intellectuals of our time"--